Constraints on southern hemisphere tropical climate change during the Little Ice Age and Younger Dryas based on glacier modeling of the Quelccaya Ice Cap, Peru. (1st October 2015) - Malone, Andrew G.O.; Pierrehumbert, Raymond T.; Lowell, Thomas V.; Kelly, Meredith A.; Stroup, Justin S.
Abstract: Improving the late Quaternary paleoclimate record through climate interpretations of low-latitude glacier length changes advances our understanding of past climate change events and the mechanisms for past, present, and future climate change. Paleotemperature reconstructions at low-latitude glaciers are uniquely fruitful because they can provide both site-specific information and enhanced understanding of regional-scale variations due to the structure of the tropical atmosphere. We produce Little Ice Age (LIA) and Younger Dryas (YD) paleoclimate reconstructions for the Huancané outlet glacier of the Quelccaya Ice Cap (QIC) and low-latitude southern hemisphere regional sea surface temperatures (SSTs) using a coupled ice-flow and energy balance model. We also model the effects of long-term changes in the summit temperature and precipitiation rate and the effects of interannual climate variability on the Huancané glacier length. We find temperature to be the dominant climate driver of glacier length change. Also, we find that interannual climate variability cannot adequately explain glacier advances inferred from the geomorphic record, necessitating that these features were formed during past colder climates. To constrain our LIA reconstruction, we incorporate the QIC ice core record, finding a LIA air temperature cooling at the ice cap of between ∼0.7 °C and ∼1.1 °C and ∼0.4 °C and regional SSTs cooling of ∼0.6 °C. For the YD paleoclimate reconstructions, we propose two limits on the precipitation rate, since the ice core record does not extend into the Pleistocene: 1) the precipitation rate scales with the Clausius-Clapeyron relationship (upper limit on cooling) and 2) the precipitation rate increases by 40% (lower limit on cooling), which is an increase about twice as great as the regional increases realized in GCM simulations for the period. The first limit requires ∼1.6 °C cooling in ice cap air temperatures and ∼0.9 °C cooling in SSTs, and the second limit requires ∼1.0 °C cooling in ice cap air temperatures and ∼0.5 °C cooling in SSTs. Our temperature reconstructions are in good agreement with the magnitude and trend of GCM simulations that incorporate the forcing mechanisms hypothesized to have caused these climate change events. Highlights: We invert the Quelccaya Ice Cap (QIC) (largest tropical ice mass) geomorphic record into a climate signal. Colder-than-present Little Ice Age at the QIC. Cold and wet Younger Drays at the QIC. Temperature is the dominant climate driver of QIC glacier length changes. Temperature sensitivity poses challenges for future of QIC given anthropogenic warming.